Oxygen doping in antimony sulfide nanosheets to facilitate catalytic conversion of polysulfides for lithium–sulfur batteries. Issue 26 (1st March 2021) - Zhang, Yonggui; Yang, Shuo; Zhou, Suya; Zhang, Libin; Gu, Binbin; Dong, Yangyang; Kong, Suzhen; Cai, Dong; Fang, Guoyong; Nie, Huagui; Yang, Zhi
Abstract : O-doped Sb2 S3 nanosheets as a high-performance catalyst can effectively mitigate the shuttle effect, achieving outstanding electrochemical performance of lithium–sulfur batteries. Abstract : A high-performance catalyst, O-doped Sb2 S3 nanosheets (SS–O NSs), is synthesized and introduced into lithium–sulfur batteries. Owing to their good conductivity, strong adsorbability/catalytic effect to polysulfides and fast Li + diffusion, the SS–O NSs-modified cathodes can effectively mitigate the shuttle effect, thus achieving outstanding electrochemical performance.